Fenrisulven sluppet løs - Grundtvig og det revolutionære demokrati i 1830 - Nygaard, Bertel (Slagmark - Tidsskrift for idéhistorie, 2018)
Often characterized as the founding father of Danish national culture and democracy during the 19th century, N.F.S. Grundtvig also formulated remarkably radical and explicit criticisms of democracy as a revolutionary and ungodly principle, against which he defended principles of strict hierarchical social order and unflinching obedience towards the absolutist monarch. These thoughts were expressed most clearly in his pamphlet Political Considerations regarding Denmark and Holstein, published in 1830-31 as a polemic against the July Revolution in France and its supporters in the Danish public sphere. However, this pamphlet also contained significant elements of unresolved contradictions pointing towards very different political modes, including democratic modes of legitimization.